A polymer PET composite board and preparation method thereof

By introducing copper complex of thiourea and modified silicon nitride into the PET composite plate, the problems of flammability and wear resistance of the PET composite plate are solved, and the excellent flame retardant, antibacterial, self-healing and wear resistance of the polymer PET composite plate are achieved.

CN119220068BActive Publication Date: 2025-04-22JIANGSU LINDEMANN NEW MATERIAL TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411730771.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-22
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Existing PET composite panels have problems such as flammability and insufficient wear resistance, resulting in short service life and safety hazards.

Method used

The thiourea ligand is reacted with copper chloride to obtain a copper thiourea copper complex, and polymerized with terephthalic acid and ethylene glycol to obtain a functionalized polyester; at the same time, pretreated silicon nitride was polymerized and grown with 1,3-di(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphophenophen-10-oxide to obtain a modified silicon nitride; then the functionalized polyester and modified silicon nitride were melt-mixed and mixed and then calendered to obtain a polymer PET composite plate.

Benefits of technology

This polymer PET composite panel has excellent flame retardant properties, anti-mildew and antibacterial properties, self-repair properties and wear resistance, extends service life and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention discloses a polymer PET composite board and a preparation method thereof, and relates to the technical field of composite materials. When preparing the polymer PET composite board, the present invention reacts 4-(2-furan)-3-thiosemicarbazide and 6-hydroxyhexanal and then reacts with cupric chloride to obtain a thiosemicarbazide copper complex; terephthalic acid, ethylene glycol, and thiosemicarbazide copper complex are polymerized to obtain functionalized polyester; 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide are polymerized and grown on pretreated silicon nitride to obtain pre-modified silicon nitride; pre-modified silicon nitride and N-(2-aminopropyl)maleimide are reacted to obtain modified silicon nitride; functionalized polyester and modified silicon nitride are melt-mixed and then calendered to obtain a polymer PET composite board. The high molecular PET composite board prepared by the invention has excellent mildew and antibacterial, flame retardant, wear-resistant and self-repairing properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, in particular to a polymer PET composite board and a preparation method thereof. Background Art

[0002] With the rapid development of the manufacturing industry of plastic products such as PET, the application of polyester polymers is no longer limited to light industries such as textiles and plastics, but has expanded to industries such as construction, transportation, decoration, and medical treatment. PET sheet is one of the products of application expansion. PET composite board is a polyester sheet prepared with polyethylene terephthalate as the main raw material. It can be used to make furniture, partitions, doors and windows and other decoration materials, touch screens, display screens and other electronic equipment materials, as well as automotive interiors, instrument panels and other components. However, ordinary PET composite boards have the problem of being easy to burn, and are also easily worn during long-term use. While bringing hidden dangers to people's life and property safety, it also shortens the service life of the PET composite board. Therefore, it is necessary to invent a PET composite board with excellent flame retardant properties and wear resistance, which can protect people's life and property safety while extending the service life of the PET composite board. Summary of the invention

[0003] The object of the present invention is to provide a polymer PET composite board and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A polymer PET composite board, wherein the polymer PET composite board is prepared by reacting a thiosemicarbazone ligand and copper chloride to obtain a thiosemicarbazone copper complex; polymerizing terephthalic acid, ethylene glycol and the thiosemicarbazone copper complex to obtain a functionalized polyester; reacting pre-modified silicon nitride and N-(2-aminopropyl)maleimide to obtain a modified silicon nitride; and calendering the functionalized polyester and the modified silicon nitride after melt mixing to obtain the polymer PET composite board;

[0006] The thiosemicarbazone ligand is prepared by reacting 4-(2-furan)-3-thiosemicarbazone and 6-hydroxyhexanal;

[0007] The pre-modified silicon nitride is prepared by polymerizing and growing 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide on pre-treated silicon nitride;

[0008] The pretreated silicon nitride is prepared by reacting silicon nitride and 3-chloropropyltriethoxysilane.

[0009] A method for preparing a polymer PET composite board, the method comprising the following preparation steps:

[0010] (1) Under nitrogen protection, the thiosemicarbazone ligand, anhydrous ethanol and chloroform were mixed evenly in a mass ratio of 1:(6-8):(6-8), and copper chloride was added in an amount 0.5 times the molar amount of the thiosemicarbazone ligand. Under nitrogen protection, the mixture was stirred at 40-50°C and 300-500 r / min for 20-24 h, and dried at 50-60°C for 8-10 h under vacuum conditions to obtain the thiosemicarbazone copper complex.

[0011] (2) Add terephthalic acid, ethylene glycol and thiosemicarbazone copper complex into a reactor in a molar ratio of 1:(0.6-0.7):(0.5-0.6), add a stabilizer in an amount of 0.06-0.08 times the mass of terephthalic acid and antimony trioxide in an amount of 0.03-0.05 times the mass of terephthalic acid, evacuate the reactor, fill with nitrogen to maintain the pressure in the reactor at 300-360 kPa, stir at 230-250°C and 300-500 r / min until the water output reaches 90% of the theoretical value, heat to 270-280°C, evacuate the reactor, maintain the pressure in the reactor below 60 Pa, continue stirring and reacting for 2-3 hours, fill with nitrogen and discharge the material to obtain a functionalized polyester;

[0012] (3) Pretreated silicon nitride, 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane, triethylamine, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(2-3):(0.03-0.05):(30-40), and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (0.7-0.8 times the molar amount of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane) was added, and the mixture was stirred at 70-80°C and 300-500 r / min for 6-8 hours. Filter, wash with anhydrous ethanol and deionized water for 3 to 5 times respectively, and dry at 50 to 60°C for 8 to 10 hours under vacuum conditions to obtain pre-modified silicon nitride; mix the pre-modified silicon nitride, N-(2-aminopropyl)maleimide, triethylamine, and toluene in a mass ratio of 1:(2 to 3):(0.03 to 0.05):(10 to 12), stir at 50 to 60°C and 300 to 500 r / min for 3 to 4 hours, filter, wash with anhydrous ethanol and deionized water for 3 to 5 times respectively, and dry at 50 to 60°C for 8 to 10 hours under vacuum conditions to obtain modified silicon nitride;

[0013] (4) The functionalized polyester and modified silicon nitride are mixed in a mass ratio of 1:(0.04-0.06), placed in a hot melt machine, stirred at 230-240°C and 300-500 r / min for 16-20 min, and then sent to a calender for calendering. After calendering, the mixture is allowed to stand at 50-60°C for 2-3 h, and naturally cooled to room temperature to obtain a polymer PET composite board.

[0014] As an optimization, the preparation method of the thiosemicarbazone ligand in step (1) is: add 4-(2-furan)-3-thiosemicarbazone and 6-hydroxyhexanal in a molar ratio of 1:1 to methanol with a mass that is 10 to 12 times that of 4-(2-furan)-3-thiosemicarbazone, stir at 50 to 60°C and 300 to 500 r / min for 20 to 24 hours, and dry at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain the thiosemicarbazone ligand.

[0015] As an optimization, the structure of the thiosemicarbazone copper complex in step (1) is:

[0016] .

[0017] As an optimization, the stabilizer in step (2) is one of triphenyl phosphate, trimethyl phosphate, and tetraethylammonium hydroxide.

[0018] As an optimization, the preparation method of the pretreated silicon nitride in step (3) is: silicon nitride and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(50~60), silane hydrolyzate is added in an amount of 8~10 times the mass of silicon nitride, the mixture is stirred at 50~60°C and 300~500r / min for 2~3h, filtered, washed with anhydrous ethanol for 3~5 times, and dried at 50~60°C under vacuum conditions for 8~10h to obtain pretreated silicon nitride.

[0019] As an optimization, the preparation method of the silane hydrolyzate is: 3-chloropropyltriethoxysilane and anhydrous ethanol are mixed evenly in a mass ratio of 1:(20~30), the pH is adjusted to 4~6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10~30°C and 300~500r / min for 50~60min to prepare a silane hydrolyzate.

[0020] As an optimization, the particle size of the silicon nitride is 1-2 μm.

[0021] As an optimization, the process parameters of the calendering molding in step (4) are: setting the calender temperature to 170-180°C, the calendering speed to 50-60m / min, and the pressure to 24-30MPa.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] When preparing a polymer PET composite board, the present invention comprises the following steps: reacting 4-(2-furan)-3-thiosemicarbazide and 6-hydroxyhexanal to obtain a thiosemicarbazide ligand; reacting the thiosemicarbazide ligand and cupric chloride to obtain a thiosemicarbazide copper complex; polymerizing terephthalic acid, ethylene glycol and the thiosemicarbazide copper complex to obtain a functionalized polyester; reacting silicon nitride and 3-chloropropyltriethoxysilane to obtain a pretreated silicon nitride; polymerizing and growing 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide on the pretreated silicon nitride to obtain a premodified silicon nitride; reacting the premodified silicon nitride and N-(2-aminopropyl)maleimide to obtain a modified silicon nitride; and calendering the functionalized polyester and the modified silicon nitride after melt mixing to obtain the polymer PET composite board.

[0024] First, 4-(2-furan)-3-thiosemicarbazide and 6-hydroxyhexanal are reacted to obtain a thiosemicarbazide ligand; the thiosemicarbazide ligand and cupric chloride are reacted to obtain a thiosemicarbazide copper complex, and a furan group and a hydroxyl group are introduced into the thiosemicarbazide copper complex; the hydroxyl group introduced into the thiosemicarbazide copper complex can participate in the polymerization reaction of polyester, the copper complex is introduced into the main chain of the polyester molecule, and the furan group is introduced into the side chain, and the copper complex can destroy the bacterial cell membrane and cell wall, interfere with the normal growth and reproduction process of bacteria, cause bacterial death, and give the polymer PET composite board excellent mildew and antibacterial properties; the furan group introduced into the side chain of the polyester molecule can undergo a Diels-Alder addition reaction with the maleimide group introduced into the modified silicon nitride to form a thermally reversible cross-linking network, inhibit the relative slip between the polyester molecular chains, and give the polymer PET composite board excellent self-healing properties and wear resistance.

[0025] Secondly, silicon nitride and 3-chloropropyltriethoxysilane are reacted to obtain pretreated silicon nitride, and chlorine atoms are introduced into the pretreated silicon nitride; 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide are polymerized and grown on the pretreated silicon nitride, and 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane is made excessive to obtain pre-modified silicon nitride, and DOPO structure and Si-O bond are alternately introduced into the pre-modified silicon nitride. The excess of siloxane retains a large amount of chloromethyl groups on the surface of the pre-modified silicon nitride; the DOPO structure contains biphenyl rings and phenanthrene ring structures in its molecular structure, especially the side phosphorus groups are introduced in the form of cyclic O=PO bonds, which are higher in thermal stability and chemical stability than general, non-annular organic phosphates, and have better flame retardant properties, giving the polymer PET composite board excellent flame retardant properties; the bond energy of the Si-O bond is greater than that of the CC bond, so compared with the CC bond, the Si-O bond needs to absorb more heat and its own vibration energy to resolve the energy of thermal decomposition of the polymer material. The introduction of the Si-O bond can further improve the flame retardant properties of the polymer PET composite board.

[0026] Finally, the chloromethyl groups retained on the surface of the pre-modified silicon nitride are reacted with the amino groups on N-(2-aminopropyl)maleimide to obtain modified silicon nitride, and maleimide groups are introduced on the modified silicon nitride. The maleimide groups introduced on the modified silicon nitride can undergo Diels-Alder addition reaction with the furan groups introduced on the side chains of the polyester molecules to form a thermally reversible cross-linking network, thereby inhibiting the relative slip between the polyester molecular chains and giving the polymer PET composite board excellent self-healing properties and wear resistance. Silicon nitride is an inorganic material with high strength, high hardness, wear resistance, high temperature resistance and other properties. Silicon nitride is modified to increase the compatibility of silicon nitride with the matrix resin and reduce the agglomeration of silicon nitride, so that silicon nitride can be evenly dispersed in the group resin, giving full play to the reinforcing effect of silicon nitride and giving the polymer PET composite board excellent wear resistance. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example

[0028] A method for preparing a polymer PET composite board, the method comprising the following preparation steps:

[0029] (1) Add 4-(2-furan)-3-thiosemicarbazide and 6-hydroxyhexanal in a molar ratio of 1:1 to methanol (10 times the mass of 4-(2-furan)-3-thiosemicarbazide), stir and react at 50°C, 300 r / min for 24 hours, and dry at 50°C for 10 hours under vacuum conditions to obtain thiosemicarbazide ligand; under nitrogen protection, mix thiosemicarbazide ligand, anhydrous ethanol and chloroform in a mass ratio of 1:6:6, add copper chloride (0.5 times the molar amount of thiosemicarbazide ligand), stir and react at 40°C, 300 r / min for 24 hours under nitrogen protection, and dry at 50°C for 10 hours under vacuum conditions to obtain thiosemicarbazide copper complex;

[0030] (2) Add terephthalic acid, ethylene glycol, and thiosemicarbazone copper complex into a reactor in a molar ratio of 1:0.6:0.5, add trimethyl phosphate in an amount of 0.06 times the mass of terephthalic acid, and antimony trioxide in an amount of 0.03 times the mass of terephthalic acid, evacuate the reactor, fill with nitrogen to maintain the pressure in the reactor at 300 kPa, stir at 230°C and 300 r / min until the water output reaches 90% of the theoretical value, raise the temperature to 270°C, evacuate the reactor, maintain the pressure in the reactor below 60 Pa, continue stirring and reacting for 3 hours, fill with nitrogen and discharge the material to obtain a functionalized polyester;

[0031] (3) 3-Chloropropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:20, the pH was adjusted to 4 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 10°C and 300 r / min for 60 min to prepare a silane hydrolyzate; silicon nitride and anhydrous ethanol were mixed at a mass ratio of 1:50, 8 times the mass of silicon nitride was added with the silane hydrolyzate, and the mixture was stirred at 50°C and 300 r / min for 3 h, filtered, washed with anhydrous ethanol for 3 times, and dried at 50°C under vacuum for 10 h to prepare a pretreated silicon nitride; pretreated silicon nitride, 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane, triethylamine, and N,N-dimethylformamide were mixed at a mass ratio of 1:2:0.03:30, and added Add 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane in a molar amount of 0.7 times that of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, stir and react at 70°C and 300 r / min for 8 hours, filter, wash with anhydrous ethanol and deionized water 3 times each, and dry at 50°C for 10 hours under vacuum conditions to obtain pre-modified silicon nitride; mix the pre-modified silicon nitride, N-(2-aminopropyl)maleimide, triethylamine, and toluene in a mass ratio of 1:2:0.03:10, stir and react at 50°C and 300 r / min for 4 hours, filter, wash with anhydrous ethanol and deionized water 3 times each, and dry at 50°C for 10 hours under vacuum conditions to obtain modified silicon nitride;

[0032] (4) The functionalized polyester and modified silicon nitride were mixed in a mass ratio of 1:0.04, placed in a hot melt machine, stirred at 230°C and 300 r / min for 20 min, and then sent to a calender for calendering. The calender temperature was set to 170°C, the calendering speed was set to 50 m / min, and the pressure was set to 24 MPa. After calendering, it was allowed to stand at 50°C for 3 h and naturally cooled to room temperature to obtain a polymer PET composite board. Example

[0033] A method for preparing a polymer PET composite board, the method comprising the following preparation steps:

[0034] (1) Add 4-(2-furan)-3-thiosemicarbazide and 6-hydroxyhexanal in a molar ratio of 1:1 to methanol (11 times the mass of 4-(2-furan)-3-thiosemicarbazide), stir and react at 55°C and 400 r / min for 22 hours, and dry at 55°C for 9 hours under vacuum conditions to obtain a thiosemicarbazide ligand; under nitrogen protection, mix the thiosemicarbazide ligand, anhydrous ethanol and chloroform in a mass ratio of 1:7:7, add copper chloride (0.5 times the molar amount of the thiosemicarbazide ligand), stir and react at 45°C and 400 r / min for 22 hours under nitrogen protection, and dry at 55°C for 9 hours under vacuum conditions to obtain a thiosemicarbazide copper complex;

[0035] (2) Add terephthalic acid, ethylene glycol, and thiosemicarbazone copper complex into a reactor at a molar ratio of 1:0.65:0.55, add trimethyl phosphate in an amount of 0.07 times the mass of terephthalic acid, and antimony trioxide in an amount of 0.04 times the mass of terephthalic acid, evacuate the reactor, fill with nitrogen to maintain the pressure in the reactor at 330 kPa, stir at 240°C and 400 r / min until the water output reaches 90% of the theoretical value, raise the temperature to 275°C, evacuate the reactor, maintain the pressure in the reactor below 60 Pa, continue stirring and reacting for 2.5 hours, fill with nitrogen and discharge the material to obtain a functionalized polyester;

[0036] (3) 3-Chloropropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:25, the pH was adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 20°C and 400 r / min for 55 min to prepare a silane hydrolyzate; silicon nitride and anhydrous ethanol were mixed at a mass ratio of 1:55, 9 times the mass of silicon nitride was added with the silane hydrolyzate, and the mixture was stirred at 55°C and 400 r / min for 2.5 h, filtered, washed with anhydrous ethanol for 4 times, and dried at 55°C under vacuum for 9 h to prepare pretreated silicon nitride; pretreated silicon nitride, 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane, triethylamine, and N,N-dimethylformamide were mixed at a mass ratio of 1:2.5:0.04:35, and added Add 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane in a molar amount of 0.75 times that of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, stir and react at 75°C and 400r / min for 7h, filter, wash with anhydrous ethanol and deionized water 4 times each, and dry at 55°C for 9h under vacuum conditions to obtain pre-modified silicon nitride; mix the pre-modified silicon nitride, N-(2-aminopropyl)maleimide, triethylamine and toluene in a mass ratio of 1:2.5:0.04:11, stir and react at 55°C and 400r / min for 3.5h, filter, wash with anhydrous ethanol and deionized water 4 times each, and dry at 55°C for 9h under vacuum conditions to obtain modified silicon nitride;

[0037] (4) The functionalized polyester and modified silicon nitride were mixed in a mass ratio of 1:0.05, placed in a hot melt machine, stirred at 235°C and 400 r / min for 18 min, and then sent to a calender for calendering. The calender temperature was set to 175°C, the calendering speed was set to 55 m / min, and the pressure was set to 27 MPa. After calendering, it was allowed to stand at 55°C for 2.5 h, and naturally cooled to room temperature to obtain a polymer PET composite board. Example

[0038] A method for preparing a polymer PET composite board, the method comprising the following preparation steps:

[0039] (1) 4-(2-furan)-3-thiosemicarbazide and 6-hydroxyhexanal were added in a molar ratio of 1:1 to methanol (12 times the mass of 4-(2-furan)-3-thiosemicarbazide), stirred at 60°C and 500 r / min for 20 h, and dried at 60°C for 8 h under vacuum to obtain a thiosemicarbazide ligand; under nitrogen protection, the thiosemicarbazide ligand, anhydrous ethanol and chloroform were mixed in a mass ratio of 1:8:8, and copper chloride (0.5 times the molar amount of the thiosemicarbazide ligand) was added, and stirred at 50°C and 500 r / min for 20 h under nitrogen protection, and dried at 60°C for 8 h under vacuum to obtain a thiosemicarbazide copper complex;

[0040] (2) Add terephthalic acid, ethylene glycol, and thiosemicarbazone copper complex into a reactor in a molar ratio of 1:0.7:0.6, add trimethyl phosphate in an amount of 0.08 times the mass of terephthalic acid, and antimony trioxide in an amount of 0.05 times the mass of terephthalic acid, evacuate the reactor, fill with nitrogen to maintain the pressure in the reactor at 360 kPa, stir at 250°C and 500 r / min until the water output reaches 90% of the theoretical value, raise the temperature to 280°C, evacuate the reactor, maintain the pressure in the reactor below 60 Pa, continue stirring and reacting for 2 hours, fill with nitrogen to discharge the material, and obtain a functionalized polyester;

[0041] (3) 3-Chloropropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:30, the pH was adjusted to 6 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 30°C and 500 r / min for 50 min to prepare a silane hydrolyzate; silicon nitride and anhydrous ethanol were mixed at a mass ratio of 1:60, 10 times the mass of silicon nitride was added with silane hydrolyzate, and the mixture was stirred at 60°C and 500 r / min for 2 h, filtered, washed with anhydrous ethanol for 5 times, and dried at 60°C under vacuum conditions for 8 h to prepare pretreated silicon nitride; pretreated silicon nitride, 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane, triethylamine, and N,N-dimethylformamide were mixed at a mass ratio of 1:3:0.05:40. Add 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide in a molar amount of 0.8 times that of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane, stir and react at 80°C, 500 r / min for 6 hours, filter, wash with anhydrous ethanol and deionized water 5 times each, dry at 60°C for 8 hours under vacuum conditions to obtain pre-modified silicon nitride; mix the pre-modified silicon nitride, N-(2-aminopropyl)maleimide, triethylamine and toluene in a mass ratio of 1:3:0.05:12, stir and react at 60°C, 500 r / min for 3 hours, filter, wash with anhydrous ethanol and deionized water 5 times each, dry at 60°C for 8 hours under vacuum conditions to obtain modified silicon nitride;

[0042] (4) The functionalized polyester and modified silicon nitride were mixed in a mass ratio of 1:0.06, placed in a hot melt machine, stirred at 240°C and 500 r / min for 16 min, and then sent to a calender for calendering. The calender temperature was set to 180°C, the calendering speed was set to 60 m / min, and the pressure was set to 30 MPa. After calendering, it was allowed to stand at 60°C for 2 h and naturally cooled to room temperature to obtain a polymer PET composite board.

[0043] Comparative Example 1:

[0044] The preparation method of the polymer PET composite board of Comparative Example 1 is different from that of Example 2 in that step (1) is not performed, and step (2) is modified as follows: terephthalic acid and ethylene glycol are added to a reaction kettle at a molar ratio of 1:1.2, trimethyl phosphate in an amount of 0.07 times the mass of terephthalic acid and antimony trioxide in an amount of 0.04 times the mass of terephthalic acid are added, vacuuming is performed, nitrogen is charged to maintain the pressure in the reaction kettle at 330 kPa, stirring at 240° C. and 400 r / min until the water output reaches 90% of the theoretical value, heating to 275° C., vacuuming is performed to maintain the pressure in the reaction kettle below 60 Pa, stirring and reacting for 2.5 h, charging with nitrogen to discharge the material, and obtaining functionalized polyester. The remaining steps are the same as those of Example 2.

[0045] Comparative Example 2:

[0046] The preparation method of the polymer PET composite board of Comparative Example 2 is different from that of Example 2 in that step (3) is different. Step (3) is modified as follows: 3-chloropropyltriethoxysilane and anhydrous ethanol are mixed uniformly at a mass ratio of 1:25, the pH value is adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 20°C and 400 r / min for 55 min to prepare a silane hydrolyzate; silicon nitride and anhydrous ethanol are mixed uniformly at a mass ratio of 1:55, silane hydrolyzate with a mass of 9 times that of silicon nitride is added, the mixture is stirred at 55°C and 400 r / min for 2.5 h, filtered, washed 4 times with anhydrous ethanol, and dried at 55°C under vacuum for 9 h. Pretreated silicon nitride was obtained; pretreated silicon nitride, 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane, triethylamine, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:2.5:0.04:35, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide with a molar amount of 0.75 times of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane was added, the mixture was stirred at 75°C and 400r / min for 7h, filtered, washed with anhydrous ethanol and deionized water 4 times each, and dried at 55°C for 9h under vacuum conditions to obtain modified silicon nitride. The remaining steps were the same as those in Example 2.

[0047] Comparative Example 3:

[0048] The preparation method of the polymer PET composite board of Comparative Example 3 is different from that of Example 2 in that step (3) is not performed, and step (4) is modified as follows: functionalized polyester and silicon nitride are mixed in a mass ratio of 1:0.05, placed in a hot melt machine, stirred at 235°C and 400r / min for 18min, and then sent to a calender for calendering, the calender temperature is set to 175°C, the calendering speed is set to 55m / min, and the pressure is set to 27MPa. After calendering, it is allowed to stand at 55°C for 2.5h, and naturally cooled to room temperature to obtain a polymer PET composite board. The remaining steps are the same as those of Example 2.

[0049] Test Example 1:

[0050] Flame retardant performance test

[0051] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T2406.2, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 1.

[0052] Table 1

[0053] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 32.13 Comparative Example 1 31.04 Example 2 32.56 Comparative Example 2 30.97 Example 3 31.92 Comparative Example 3 23.48

[0054] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the high molecular weight PET composite board prepared by the present invention has good flame retardant properties.

[0055] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that silicon nitride and 3-chloropropyltriethoxysilane are reacted to prepare pretreated silicon nitride, and chlorine atoms are introduced into the pretreated silicon nitride; 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide are polymerized and grown on the pretreated silicon nitride to prepare pre-modified silicon nitride, and DOPO structure and Si-O bond are alternately introduced into the pre-modified silicon nitride; The OPO structure contains biphenyl ring and phenanthrene ring structures in its molecular structure, especially the side phosphorus group is introduced in the form of a cyclic O=PO bond, which has higher thermal stability and chemical stability than general, non-cyclic organic phosphates, and better flame retardancy, giving the polymer PET composite board excellent flame retardancy; the bond energy of the Si-O bond is greater than that of the CC bond, so compared with the CC bond, the Si-O bond needs to absorb more heat and its own vibration energy to resolve the energy of thermal decomposition of the polymer material. The introduction of the Si-O bond can further improve the flame retardancy of the polymer PET composite board.

[0056] Test Example 2:

[0057] Test of anti-mildew and antibacterial properties

[0058] Test method: The examples and comparative examples were cut into 10 mm × 10 mm × 5 mm samples and sterilized by ultraviolet irradiation for 3 h; the Escherichia coli strains were activated and prepared to a concentration of 3 × 10 4 cfu / ml bacterial suspension; put the sample into the bacterial suspension, shake at 300r / min for 5min at room temperature, take 1ml of the bacterial suspension and dilute it to 100 times, take 1ml of the diluted bacterial suspension and inoculate it into agar medium, culture it at 37℃ for 16h, count the colonies according to the method in GB / T15979, and calculate the antibacterial rate. The results are shown in Table 2.

[0059] Table 2

[0060] Antibacterial rate (%) Antibacterial rate (%) Example 1 99.63 Comparative Example 1 72.79 Example 2 99.71 Comparative Example 2 99.58 Example 3 99.68 Comparative Example 3 99.54

[0061] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the polymer PET composite board prepared by the present invention has good antibacterial properties.

[0062] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that 4-(2-furan)-3-thiosemicarbazide and 6-hydroxyhexanal are reacted to obtain a thiosemicarbazide ligand; a thiosemicarbazide ligand and cupric chloride are reacted to obtain a thiosemicarbazide copper complex, and a furan group and a hydroxyl group are introduced into the thiosemicarbazide copper complex; the hydroxyl group introduced into the thiosemicarbazide copper complex can participate in the polymerization reaction of the polyester, and the copper complex is introduced into the main chain of the polyester molecule. The copper complex can destroy the bacterial cell membrane and cell wall, interfere with the normal growth and reproduction process of the bacteria, and cause the death of the bacteria, thereby giving the polymer PET composite board excellent mildew and antibacterial properties.

[0063] Test Example 3:

[0064] Wear resistance and self-healing performance testing

[0065] Wear resistance test method: The wear rates of the examples and comparative examples were tested according to GBIT3960. The results are shown in Table 3.

[0066] Self-repairing performance test method: Prepare the embodiment and the comparative example into standard specimens according to GB / T1040.1, test their original tensile strength with a tensile machine, then cut a 2mm deep and 20mm long crack in the middle of the unstretched original specimen, put it in a mold, keep it at 65℃ for 6h, cool it to room temperature and let it stand for 10h to obtain the repaired specimen. Test its tensile strength with a tensile machine. Calculate the self-repairing rate of the embodiment and the comparative example before and after repair, self-repairing rate = (tensile strength of the specimen after repair / original tensile strength of the specimen) × 100%. The results are shown in Table 3.

[0067] Table 3

[0068] Wear rate (%) Self-repair rate (%) Wear rate (%) Self-repair rate (%) Example 1 1.342 96.65 Comparative Example 1 2.183 57.17 Example 2 1.287 96.82 Comparative Example 2 2.259 59.82 Example 3 1.293 96.73 Comparative Example 3 2.944 56.49

[0069] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the polymer PET composite board prepared by the present invention has good wear resistance and self-repairing performance.

[0070] By comparison, the wear rates of Examples 1 to 3 are lower than that of Comparative Example 1, and the self-repair rates of Examples 1 to 3 are higher than that of Comparative Example 1, indicating that 4-(2-furan)-3-thiosemicarbazide and 6-hydroxyhexanal are reacted to obtain a thiosemicarbazide ligand; the thiosemicarbazide ligand and cupric chloride are reacted to obtain a thiosemicarbazide copper complex, and a furan group and a hydroxyl group are introduced into the thiosemicarbazide copper complex; the hydroxyl group introduced into the thiosemicarbazide copper complex can participate in the polymerization reaction of the polyester, and a furan group is introduced into the side chain of the polyester molecule. The furan group introduced into the side chain of the polyester molecule can undergo a Diels-Alder addition reaction with the maleimide group introduced into the modified silicon nitride to form a thermally reversible cross-linked network, thereby inhibiting the relative slip between the polyester molecular chains and giving the polymer PET composite board excellent self-repairing properties and wear resistance.

[0071] By comparison, the wear rates of Examples 1 to 3 are less than the wear rates of Comparative Examples 2 to 3, and the self-repair rates of Examples 1 to 3 are greater than the self-repair rates of Comparative Examples 2 to 3, indicating that pretreated silicon nitride is prepared by reacting silicon nitride and 3-chloropropyltriethoxysilane, and chlorine atoms are introduced into the pretreated silicon nitride; 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide are polymerized and grown on the pretreated silicon nitride, and 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane is made excessive to prepare pre-modified silicon nitride. Silicon nitride, an excess of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane retains a large amount of chloromethyl groups on the surface of pre-modified silicon nitride; the chloromethyl groups retained on the surface of the pre-modified silicon nitride react with the amino groups on N-(2-aminopropyl)maleimide to obtain modified silicon nitride, and maleimide groups are introduced into the modified silicon nitride. The maleimide groups introduced into the modified silicon nitride can undergo Diels-Alder addition reaction with the furan groups introduced into the side chains of polyester molecules to form a thermally reversible cross-linking network, thereby inhibiting the relative slip between polyester molecular chains and giving the polymer PET composite board excellent self-healing properties and wear resistance.

[0072] By comparison, the wear rate of Comparative Example 2 is less than that of Comparative Example 3, indicating that silicon nitride is an inorganic material with properties such as high strength, high hardness, wear resistance, and high temperature resistance. Silicon nitride is modified to increase the compatibility of silicon nitride with the matrix resin and reduce the agglomeration of silicon nitride, so that silicon nitride can be evenly dispersed in the matrix resin, giving full play to the reinforcing effect of silicon nitride, and giving the polymer PET composite board excellent wear resistance.

[0073] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A polymer PET composite board, characterized in that: The polymer PET composite board is prepared by reacting a thiosemicarbazone ligand and copper chloride to obtain a thiosemicarbazone copper complex; polymerizing terephthalic acid, ethylene glycol and the thiosemicarbazone copper complex to obtain a functional polyester; reacting pre-modified silicon nitride and N-(2-aminopropyl)maleimide to obtain modified silicon nitride; and calendering the functionalized polyester and the modified silicon nitride after melting and mixing to obtain the polymer PET composite board. The thiosemicarbazone ligand is prepared by reacting 4-(2-furan)-3-thiosemicarbazone and 6-hydroxyhexanal; The pre-modified silicon nitride is prepared by polymerizing and growing 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide on pre-treated silicon nitride; The pretreated silicon nitride is prepared by reacting silicon nitride and 3-chloropropyltriethoxysilane.

2. A method for preparing a polymer PET composite board, characterized in that: The preparation method of the polymer PET composite board comprises the following preparation steps: (1) Under nitrogen protection, the thiosemicarbazone ligand, anhydrous ethanol and chloroform were mixed evenly in a mass ratio of 1:(6-8):(6-8), and copper chloride was added in an amount 0.5 times the molar amount of the thiosemicarbazone ligand. Under nitrogen protection, the mixture was stirred at 40-50°C and 300-500 r / min for 20-24 h, and dried at 50-60°C for 8-10 h under vacuum conditions to obtain the thiosemicarbazone copper complex. (2) Add terephthalic acid, ethylene glycol and thiosemicarbazone copper complex into a reactor in a molar ratio of 1:(0.6-0.7):(0.5-0.6), add a stabilizer in an amount of 0.06-0.08 times the mass of terephthalic acid and antimony trioxide in an amount of 0.03-0.05 times the mass of terephthalic acid, evacuate the reactor, fill with nitrogen to maintain the pressure in the reactor at 300-360 kPa, stir at 230-250°C and 300-500 r / min until the water output reaches 90% of the theoretical value, heat to 270-280°C, evacuate the reactor, maintain the pressure in the reactor below 60 Pa, continue stirring and reacting for 2-3 hours, fill with nitrogen and discharge the material to obtain a functionalized polyester; (3) Pretreated silicon nitride, 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane, triethylamine, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(2-3):(0.03-0.05):(30-40), 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (0.7-0.8 times the molar amount of 1,3-bis(chloromethyl)-1,1,3,3-tetramethyldisiloxane) was added, and the mixture was stirred at 70-80°C and 300-500 r / min for 6-8 hours, filtered, washed with anhydrous ethanol and deionized water for 3-5 times respectively, and dried at 50-60°C under vacuum conditions for 8-10 hours to obtain pre-modified silicon nitride; Pre-modified silicon nitride, N-(2-aminopropyl)maleimide, triethylamine and toluene are uniformly mixed in a mass ratio of 1:(2-3):(0.03-0.05):(10-12), stirred at 50-60°C and 300-500 r / min for 3-4 hours, filtered, washed with anhydrous ethanol and deionized water for 3-5 times respectively, and dried at 50-60°C under vacuum conditions for 8-10 hours to obtain modified silicon nitride; (4) The functionalized polyester and modified silicon nitride are mixed in a mass ratio of 1:(0.04-0.06), placed in a hot melt machine, stirred at 230-240°C and 300-500 r / min for 16-20 min, and then sent to a calender for calendering. After calendering, the mixture is allowed to stand at 50-60°C for 2-3 h, and naturally cooled to room temperature to obtain a polymer PET composite board.

3. The method for preparing a polymer PET composite board according to claim 2, characterized in that: The preparation method of the thiosemicarbazone ligand in step (1) is as follows: 4-(2-furan)-3-thiosemicarbazone and 6-hydroxyhexanal are added in a molar ratio of 1:1 to methanol with a mass that is 10 to 12 times that of 4-(2-furan)-3-thiosemicarbazone, and the mixture is stirred at 50 to 60° C. and 300 to 500 r / min for 20 to 24 hours, and then dried at 50 to 60° C. under vacuum conditions for 8 to 10 hours to obtain the thiosemicarbazone ligand.

4. The method for preparing a polymer PET composite board according to claim 2, characterized in that: The structure of the thiosemicarbazone copper complex in step (1) is: 。 5. The method for preparing a polymer PET composite board according to claim 2, characterized in that: The stabilizer in step (2) is one of triphenyl phosphate, trimethyl phosphate and tetraethylammonium hydroxide.

6. The method for preparing a polymer PET composite board according to claim 2, characterized in that: The preparation method of the pretreated silicon nitride in step (3) is as follows: silicon nitride and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(50-60), silane hydrolyzate is added in an amount of 8-10 times the mass of silicon nitride, the reaction is carried out at 50-60°C and 300-500 r / min with stirring for 2-3 hours, the reaction is filtered, the reaction is washed with anhydrous ethanol for 3-5 times, and the reaction is dried at 50-60°C under vacuum conditions for 8-10 hours to obtain the pretreated silicon nitride.

7. The method for preparing a polymer PET composite board according to claim 6, characterized in that: The preparation method of the silane hydrolyzate is as follows: 3-chloropropyltriethoxysilane and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(20-30), the pH value is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10-30° C. and 300-500 r / min for 50-60 min to prepare the silane hydrolyzate.

8. The method for preparing a polymer PET composite board according to claim 6, characterized in that: The particle size of the silicon nitride is 1-2 μm.

9. The method for preparing a polymer PET composite board according to claim 2, characterized in that: The process parameters of the calendering molding in step (4) are: setting the calender temperature to 170-180°C, the calendering speed to 50-60m / min, and the pressure to 24-30MPa.

Citation Information

Patent Citations

  • Flame-retardant compound, method for producing same, resin composition, and product thereof

    CN113980051A

  • Maleimide resin composition, prepreg, laminate, resin film, printed wiring board, and semiconductor package

    CN116507487A